Inactivation of Herpes Simplex Virus by Photosensitizing Anthraquinones Isolated from Heterophyllaea pustulata - Mugas, M. Laura; Marioni, Juliana; Martinez, Florencia; Aguilar, Juan J.; Cabrera, José L.; Contigiani, Marta S.; Konigheim, Brenda S.; Núñez-Montoya, Susana C. (Planta Medica, 2021)
Heterophyllaea pustulata is a phototoxic plant from Argentina. Aerial parts extracts, high in photosensitizing anthraquinones, have shown in vitro antiviral activity. The purpose of this study was to study the antiherpetic activity of the main purified anthraquinones, even evaluating their competence as photodynamic sensitizers to photo-stimulate the antiviral effect. In vitro antiviral activity against Herpes Simplex virus type I and the photo-inactivation of viral particle were studied by the Neutral Red uptake test and observation of the cytopathic effect. Rubiadin 1-methyl ether and 5,5′-bisoranjidiol produced a significant effect (≥ 80% inhibition) with minimal damage to host cells (subtoxic concentration). Anthraquinones with poor antiherpetic activity at its maximum noncytotoxic concentration showed an important photo-stimulated effect, such is the case of soranjidiol and 5,5′-bisoranjidiol (28.0 ± 6.3 vs. 81.8 ± 2.1% and 15.5 ± 0.3 vs. 89.8 ± 1.7%, respectively). The study also proved the decrease of viral particles, necessary to reduce infection. Therefore, photosensitizing anthraquinones from natural resources could be proposed to develop new treatments for localized viral lesions with antimicrobial photodynamic therapy.
Keywords: Heterophyllaea pustulata; Rubiaceae; anthraquinones; Herpes Simplex virus type I; photo-inactivation; antiviral activity; antimicrobial photodynamic therapy